HAK POLITIK PEREMPUAN DALAM ISLAM (Usaha Memahami Nash Secara Kontekstual) - Nelli, Jumni (MUWAZAH, 2013)
Abstract : There are two opposite opinions about the permissibility of women in politics. One opinion states that women should be at home, devoted to her husband, just have a domestic role, and should not be involved in politics. Another opinion states that women have the freedom to play, both inside and outside the home as well as in politics. This happens because they don’t understand the concept of women's rights that purely political, as well as in understanding the text verse Al-Qur`an is still gender bias. The differences of those opinions related to the differences in understanding the Islamic sources especially the verses of the Al-Qur`an about politics. This paper discusses political rights of women in Islam, so that people can understand and not considered taboo against women who were involved in politics. Based on the identification, classification, and analysis of the texts of the Al-Qur'an and hadith about politics, found that women in politics have the right according to Islam. Men and women are obliged to enjoining good and forbidding evil through several ways including the political media. Islam does not distinguish between men and women in individual rights and social rights especially political rights. However, it was noted that all rights must be placed within the limits of natural as women.       Abstrak : Terjadi dua pendapat yang berseberangan tentang kebolehan perempuan berpolitik.  Satu pendapat menyatakan perempuan harus di dalam rumah, mengabdi kepada suami, dan hanya mempunyai peran domestik dan tidak boleh berpolitik. Pendapat  lain menyatakan perempuan mempunyai kemerdekaan untuk berperan, baik di dalam maupun di luar rumah demikian juga dalam bidang politik. Hal tersebut terjadi karena belum difahaminya konsep tentang hak politik perempuan secara murni, juga karena dalam memahami teks ayat al-Qur`an masih bias gender. Perbedaan pandangan tersebut terkait dengan perbedaan dalam memahami sumber-sumber ajaran Islam  terutama ayat al-Qur`an yang berbicara tentang politik. Makalah ini  membahas  bagaimana sebenarnya hak politik perempuan dalam Islam, sehingga masyarakat dapat memahami dan tidak menganggap tabu terhadap perempuan yang terjun di dunia politik. Berdasarkan  identifikasi dan klasifikasi serta analisis  nash-nash dari  al-Qur’an dan hadis tentang politik dalam al-Qur`an, ditemukan bahwa perempuan mempunyai hak dalam berpolitik menurut Islam. Laki-laki dan perempuan berkewajiban untuk amar makrûf nahî munkar melalui beberapa cara termasuk diantaranya dengan media politik. Islam tidak membedakan laki-laki dan perempuan dalam hak-hak individu dan hak-hak kemasyarakatan utamanya hak politik. Namun demikian, yang perlu dicatat adalah semua hak tersebut harus diletakkan dalam batas-batas kodrati sebagai perempuan.